Strain engineering of antimonene by a first-principles study : mechanical and electronic properties - Kripalani, Devesh Raju (2020)
Recent success in the experimental isolation and synthesis of highly stable atomically thin antimonene has triggered great interest into examining its potential role in nanoelectronic applications. In this work, we investigate the mechanical and electronic properties of monolayer antimonene in its most stable β-phase using first-principles calculations. The upper region of its valence band is found to solely consist of lone pair p-orbital states, which are by nature more delocalized than the d-orbital states in transition metal dichalcogenides, implying superior transport performance of antimonene. The Young's and shear moduli of β-antimonene are observed to be ∼25% higher than those of bulk antimony, while the hexagonal lattice constant of the monolayer reduces significantly (∼5%) from that in bulk, indicative of strong interlayer coupling. The ideal tensile test of β-antimonene under applied uniaxial strain highlights ideal strengths of 6 and 8 GPa, corresponding to critical strains of 15% and 17% in the zigzag and armchair directions, respectively. During the deformation process, the structural integrity of the material is shown to be better preserved, albeit moderately, in the armchair direction. Interestingly, the application of uniaxial strain in the zigzag and armchair directions unveil direction-dependent trends in the electronic band structure. We find that the nature of the band gap remains insensitive to strain in the zigzag direction, while strain in the armchair direction activates an indirect-direct band gap transition at a critical strain of 4%, owing to a band switching mechanism. The curvature of the conduction band minimum increases during the transition, which suggests a lighter effective mass of electrons in the direct-gap configuration than in the free-standing state of equilibrium. The work function of free-standing β-antimonene is 4.59 eV, and it attains a maximum value of 5.07 eV under an applied biaxial strain of 4%. The findings reported in this work provide fundamental insights into the mechanical behavior and strain-tunable nature of the electronic properties of monolayer β-antimonene, in support of its promising role for future nanoelectromechanical systems and optoelectronic applications.